Silencing Primary Dystonia: Lentiviral-Mediated RNA Interference Therapy for DYT1 Dystonia - Gonzalez-Alegre, Pedro (J Neurosci, 2005)
DYT1 is the most common inherited dystonia. Currently, there are no preventive or curative therapies for this dominantly inherited disease. DYT1 dystonia is caused by a common three-nucleotide deletion in the TOR1A gene that eliminates a glutamic acid residue from the protein torsinA. Recent studies suggest that torsinA carrying the disease-linked mutation, torsinA(ΔE) acts through a dominant-negative effect by recruiting wild-type torsinA [torsinA(wt)] into oligomeric structures in the nuclear envelope. Therefore, suppressing torsinA(ΔE) expression through RNA interference (RNAi) could restore the normal function of torsinA(wt), representing a potentially effective therapy regardless of the biological role of torsinA. Here, we have generated short hairpin RNAs (shRNAs) that mediate allele-specific suppression of torsinA(ΔE) and rescue cells from its dominant-negative effect, restoring the normal distribution of torsinA(wt). In addition, delivery of this shRNA by a recombinant feline immunodeficiency virus effectively silenced torsinA(ΔE) in a neural model of the disease. We further establish the feasibility of this viral-mediated RNAi approach by demonstrating significant suppression of endogenous torsinA in mammalian neurons. Finally, this silencing of torsinA is achieved without triggering an interferon response. These results support the potential use of viral-mediated RNAi as a therapy for DYT1 dystonia and establish the basis for preclinical testing in animal models of the disease.